1986
DOI: 10.1002/ffj.2730010404
|View full text |Cite
|
Sign up to set email alerts
|

Additional neutral volatiles from litchi (Litchi chinensis sonn.) fruit

Abstract: The volatiles from fresh litchi (Litchi chinemis Sonn.) fruit pulp were separated by standard controlled high-vacuum distillation with subsequent solvent extraction (pentane-dichloromethane, 2: 1) and silica gel liquid chromatography pre-separation using a pentane-diethyl ether gradient. Polar fruit constituents were separated by chloroform extraction and subsequent liquid-liquid distribution. The concentrates were analysed by capillary gas chromatography (HRGC) and coupled HRGC techniques, i.e. on-line capill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Other noteworthy FID peaks observed include hexanal, cis-rose oxide, citronellal, linalool, geraniol, and 2-phenyl ethanol. These volatiles have been reported in at least one of the earlier GC-MS studies (3,5,6). However, compounds that produced small FID peaks without characteristic MS spectra such as (E)-2nonenal and (E,E)-2,4-decadienal were not reported until GC-O was employed (4).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Other noteworthy FID peaks observed include hexanal, cis-rose oxide, citronellal, linalool, geraniol, and 2-phenyl ethanol. These volatiles have been reported in at least one of the earlier GC-MS studies (3,5,6). However, compounds that produced small FID peaks without characteristic MS spectra such as (E)-2nonenal and (E,E)-2,4-decadienal were not reported until GC-O was employed (4).…”
Section: Resultsmentioning
confidence: 91%
“…Other investigators (3,4) have described its odor/aroma as sweet, rose-floral, and citrus-like. Previous studies identified many of the free or neutral volatiles in this fruit (3)(4)(5)(6). Johnston and co-workers (3) identified 42 volatiles in freshly macerated lychee from Florida.…”
Section: Introductionmentioning
confidence: 97%
“…Johnston et al (1980) were the first to report on the volatiles of lychee, suggesting the citrus flavor was due to the presence of compounds such as geranial and neral and its floral note was due mainly to 2-phenylethanol. Two other papers, subsequently published, reported headspace and neutral volatiles in this fruit (Toulemonde and Beauverd, 1985;Froehlich and Schreier, 1986). Among the volatiles identified, limonene, rose oxide, nonanal, decanal, citronellol, and geraniol were considered to be significant for the fruityfloral and citrus notes of the fruit.…”
Section: Introductionmentioning
confidence: 81%
“…Several previous studies have explored the volatile composition of fresh litchi fruit, as well as frozen litchi , , dried litchi , and canned litchi . However, some of these researches did not cover the cultivar of litchi ,, , and some investigated only a few cultivars ,,, or only performed qualitative identification of volatiles . It remains unclear which volatile components are similar and which are unique, and what the volatile profile characters are among different commercially cultivated litchi cultivars.…”
Section: Introductionmentioning
confidence: 99%